2014
DOI: 10.2166/wst.2014.161
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature and salt on metal and sediment removal in stormwater biofilters

Abstract: Stormwater biofilters are used to treat stormwater runoff. In countries with cold winter climates, biofilters are subject to low temperatures which, in some cases, are combined with potentially high salt concentrations from road de-icing, potentially affecting the biofilter's performance. Since stormwater biofilters have been developed without consideration of their critical winter use, a laboratory study was carried out to evaluate the performance of stormwater biofilters subjected to low and high temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Additionally, [20,27] reported that metals adsorbed on soils designed for bioretention were scarcely leached due to NaCl applications and, therefore, retention under cold climate conditions is likely to be effective for the studied purpose. However, [28] detected a significant impact of salt addition on the removal of dissolved Pb and Cu, which might be due to the fact that the salt favors dissolution of organic matter which has a strong affinity of these metals. In the present study, a high release of Ni (9%-15%) from the charcoal amended filter was detected.…”
Section: Desorption Of Metals Due To Saltsmentioning
confidence: 99%
“…Additionally, [20,27] reported that metals adsorbed on soils designed for bioretention were scarcely leached due to NaCl applications and, therefore, retention under cold climate conditions is likely to be effective for the studied purpose. However, [28] detected a significant impact of salt addition on the removal of dissolved Pb and Cu, which might be due to the fact that the salt favors dissolution of organic matter which has a strong affinity of these metals. In the present study, a high release of Ni (9%-15%) from the charcoal amended filter was detected.…”
Section: Desorption Of Metals Due To Saltsmentioning
confidence: 99%
“…() and Søberg et al . () followed the general guidance offered by Caraco and Claytor () and Muthanna et al . ().…”
Section: Methodsmentioning
confidence: 99%
“…Their review did not include salt as an LID concern. Other studies have found that bioretention does not retain salt (Khan et al ., ; Soberg et al ., ); that salt in bioretention systems increases heavy metal release (Soberg et al ., ); and that salt affects bacterial communities subsequently affecting the uptake potential in a bioretention system (Endreny et al ., ). Further, studies have shown salt use within a watershed can be a chronic issue for both surface and groundwater and is not limited to winter conditions (Perera et al ., ; Corsi et al ., ).…”
Section: Introductionmentioning
confidence: 97%